Ação antinociceptiva do Cyclo(Gly-Pro) sobre a dor orofacial em roedores - Barbosa, Breno Ferreira (2014)
Cyclo(Gly-Pro)(CGP) is a dipeptide that can be extracted from the fungus Rhizoctonia sp. or synthesized. The Rhizoctonia is a derived the kingdom Fungi, whose representatives inhabiting endophytic soil organisms of various vegetables genre. Among the plants possessing this fungus, deserves mastic-red (Schinus terebinthifolius Raddi) which is popularly used for different purposes, including inflammation. Thus, the aim of this study was to evaluate the possible antinocicetivo action on orofacial pain of Cyclo(Gly-Pro) in rodents. To this end, 90 male Swiss mice (25 to 35g) with 2 to 3 months were used. The animals were divided into groups and were treated with CGP concentrations of 0.1 , 1 and 10 mg / kg administered intraperitoneally (i.p.) , vehicle (0.9% saline solution, i.p.) or standard drug (i.p.) . In order to evaluate the effects of CGP on orofacial nociception tests orofacial pain formalin (2%), capsaicin and glutamate - induced were performed. The motor coordination of the animals was assessed by testing the spontaneous movement. Results were expressed as mean ± SEM Differences between groups were analyzed using the analysis of variance ANOVA, one-way, and followed by Tukey test. P values < 0.05 were considered statistically significant. In the three nociceptive orofacial test, CGP produced a significant reduction (p < 0.001) in the orofacial region of friction time when compared to the control goup, plus there is some significant difference between groups (p <0.01). No changes were observed in the test of spontaneous movement. Thus, it is concluded that the CGP has antinociceptive and that the spontaneous movement test, the CGP was not able to alter motor coordination of animals in the doses evaluated.